Preliminary monitoring of concentration of particulate matter (PM(2.5)) in seven townships of Yangon City, Myanmar - Yi, Ei Ei Pan Nu (Environ Health Prev Med, 2018)
BACKGROUND: Airborne particulate pollution is more critical in the developing world than in the developed countries in which industrialization and urbanization are rapidly increased. Yangon, a second capital of Myanmar, is a highly congested and densely populated city. Yet, there is limited study which assesses particulate matter (PM(2.5)) in Yangon currently. Few previous local studies were performed to assess particulate air pollution but most results were concerned PM(10) alone using fixed monitoring. Therefore, the present study aimed to assess distribution of PM(2.5) in different townships of Yangon, Myanmar. This is the first study to quantify the regional distribution of PM(2.5) in Yangon City. METHODS: The concentration of PM(2.5) was measured using Pocket PM(2.5) Sensor (Yaguchi Electric Co., Ltd., Miyagi, Japan) three times (7:00 h, 13:00 h, 19:00 h) for 15 min per day for 5 days from January 25(th) to 29(th) in seven townships. Detailed information of eight tracks for PM(2.5) pollution status in different areas with different conditions within Kamayut Township were also collected. RESULTS: The results showed that in all townships, the highest PM(2.5) concentrations in the morning followed by the evening and the lowest concentrations in the afternoon were observed. Among the seven townships, Hlaingtharyar Township had the highest concentrations (164 ± 52 μg/m(3)) in the morning and (100 ± 35 μg/m(3)) in the evening. Data from eight tracks in Kamayut Township also indicated that PM(2.5) concentrations varied between different areas and conditions of the same township at the same time. CONCLUSION: Myanmar is one of the few countries that still have to establish national air quality standards. The results obtained from this study are useful for the better understanding of the nature of air pollution linked to PM(2.5). Moreover, the sensor which was used in this study can provide real-time exposure, and this could give more accurate exposure data of the population especially those subpopulations that are highly exposed than fixed station monitoring.